Determinants of IgG antibodies kinetics after severe and critical COVID‐19. Issue 9 (12th May 2021) - De Greef, Julien; Scohy, Anaïs; Zech, Francis; Aboubakar, Frank; Pilette, Charles; Gerard, Ludovic; Pothen, Lucie; Yildiz, Halil; Belkhir, Leïla; Yombi, Jean Cyr
Abstract: The kinetics of IgG antibodies after coronavirus disease 2019 (COVID‐19) remain poorly understood. We investigated factors influencing severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) IgG antibody levels and time to seronegativation during the follow‐up of severe and critically ill patients. We retrospectively reviewed serological evaluations drawn during the follow‐up of severe or critical laboratory‐proven COVID‐19 patients hospitalized at a large academic hospital. Specific IgG titers were measured using a chemiluminescent assay targeting anti‐spike and anti‐nucleocapsid protein IgG. The influence of time, demographic factors, clinical and paraclinical characteristics, and COVID‐19 therapeutics on IgG levels were assessed through linear regression using a mixed‐effect model, and delay until IgG negativation through a Weibull regression model. The cohort included 116 patients with a total of 154 IgG measurements drawn at a median of 79 days after diagnosis. IgG antibodies were increased with age ( p  = 0.005) and decreased significantly over time ( p  = 0.0002). Using elapsed time and age as covariates, we demonstrated higher IgG levels in patients with a higher body mass index (BMI) ( p  = 0.0026) and lower IgG levels in immunocompromised patients ( p  = 0.032). A high BMI was further found to delay and immunodeficiency to hasten significantly seronegativation, whereas no significant effect was observed with corticosteroids. These data highlight the waning over time of IgG antibodies after severe or critical COVID‐19. Age, BMI, and immunosuppression also appear to influence the IgG kinetics, while short‐term corticotherapy does not. Those data improve the understanding of SARS‐CoV‐2 serology while further research should determine the determinants of long‐term seroprotection. Highlights: Anti‐SARS‐CoV‐2 IgG antibody levels measured during follow‐up of severe and critical COVID‐19 were studied. We analyzed the influence of time, demographics, clinical and paraclinical characteristics and COVID‐19 treatments on specific IgG levels and time to seronegativation. Time and immunodepression were associated to reduced IgG levels at follow‐up, while age and BMI were associated to increased levels. Corticosteroids given as short‐term treatment for COVID‐19 did not show influence. BMI and immunodepression were respectively associated with decreased and increased rates of seronegativation.